Kiss and be Friends: A note on the use of the verb-form be in the present tense. - Falk, Lilian (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1988)
The paper examines a number of attested citations with the form be used to denote action or state in the present, rather than the standard am/are/is. The expression I look in their eyes and be honest (rather than the Standard am honest) and similar expressions are discussed in the light of the current controversy concerning the notion of ’grammaticalness’ and ’acceptibility’ of pragamatic speech acts. The view supported in this paper is that these expressions should be considered as grammatical.